The purpose of 1 Thessalonians - Cornelius, Elma M. (HTS teologiese studies, 2001)
The purpose of a text is related to its rhetorical genre, but it is important to realise that genre is more than the form and function of discourse. Genre derives from and is relate4 to the author's motive in responding to a recurrent social situation. These situations and responses are seen as resulting from shared social interpretations and are part of a socially constructed reality. Not only do genres respond to particular social contexts, they also shape them. The aim of this article is to interpret the purpose of 1 Thessalonians. It is concluded that the stated purpose of 1 Thessalonians is found in 3:11 and 12 and 5:23: to persuade the readers to live according to God's will The author teaches the readers how to live as Christians and encourages them to accept new roles in society, to change their lives according to God's will and to remain faithful to Christ and the author, regardless of the hardships and opposition that they encounter.